Approach to Choose of Optimal Number of Turns in Planar Spiral Coils for Systems of Wireless Power Transmission - Krestovnikov, Konstantin; Cherskikh, Ekaterina; Bykov Аleksandr (Elektronika ir Elektrotechnika, 2020)
Correct choice of coil parameters for resonant circuits in inductive power transmission systems is a relevant problem, as it significantly influences the efficiency and transmitted power in the systems and provides for optimization of these parameters. This paper presents a methodology of calculation of geometrical and electrical parameters and approach to choose the optimal number of turns in planar coils used in the wireless power transmission (WPT) system with parallel resonant circuit. Formulas are derived for calculation of active resistance and inductance of the coil, normalized to the specified design parameters of the coil. Connection is made between the design and electrical parameters of the coil, which allows choosing the optimal number of turns according to different criteria and guard conditions. The examples of practical use of the chosen approach with transmitting and receiving coils of WPT system are presented. The obtained results show that efficiency and transmitted power in the system are higher when using the coils with the calculated number of turns. The proposed approach may be used in selection of optimal design of loop coils in systems with fixed frequency, and in systems, whose operational frequency depends on the parameters of the resonant circuit.